Perceptions of Udinus Students from Outside the Region Toward Traditional Cuisine of Semarang City - Prima Setia Judha Pranatha; Izza Ulumuddin Ahmad Asshofi; Emik Rahayu; Cindy Citya Dima (Badan Penerbit STIEPARI Press, 2025)
This research aims to explore the perceptions of students from outside the area at Udinus towards traditional food in the city of Semarang, as well as the factors that influence their perceptions. This research uses mixed methods where the results obtained are based on observations, interviews and questionnaires. This research was conducted on 87 students from outside the region at Dian Nuswantoro University who were selected purposively based on certain criteria. Research data was collected using interview guidelines, questionnaires prepared based on the problem formulation and research instruments. Research data was analyzed using thematic analysis, namely analysis that identifies, codes, and interprets themes that emerge from the data. The results of the research show that the perceptions of students outside the Udinus area towards traditional Semarang city cuisine vary, ranging from strongly agree, agree, disagree and disagree. There are several factors that can influence their perceptions, namely their cultural and culinary background, experience and frequency of consuming traditional Semarang city cuisine, knowledge and information about the cuisine, as well as social factors, such as friends, family and the media. Their perceptions also have an impact on their behavior in choosing and consuming traditional Semarang city cuisine, as well as their social and cultural integration on the Udinus campus. It is hoped that this research can provide additional input for the development of social sciences, especially in the field of culinary anthropology.